Electro-acoustic Dance composition: Practicality and pragmatism - Ian Evans Guthrie (Journal of the Association for Technology in Music Instruction, 2025)
“Efficiency, expediency, and experimentation in Dance Compositions.” In this presentation, I want to describe the practical difficulties in composing for dance and using live electronics, and how I have found a happy medium. The presentation will begin with an overview of common dance approaches as I have experienced at the Interlochen Center for the Arts, the Kansas City Ballet, and the Florida State University School of Dance, and other institutions. Then, I will discuss the limitations for elaborate electroacoustic setups, particularly in the “black box” theatres and variety of dance studios used at these places. I will defend my thesis that fixed media compositions are by far the most versatile works for dance. I will then give a brief history of works that use variables in dance. With the exception of the Cage and post-Cage chance music (a tradition continued by Stephen Montague and others, including myself in some of my dance compositions), many dancers prefer works that are fixed, or at least predictable and repetitive. After the historical overview, I will quickly share my experience with my preferred alternative: fixed media. For the demonstration on how I have created the illusion of live electronic manipulations, I will give a miniature lecture recital using my most recent dance composition for piano and fixed media, entitled "Hidden Elements." Despite the simple approach, it nonetheless allowed my music to be adaptable to nearly any dance space, no matter their setup (beyond a basic speaker system). Indeed, this was a work where I desired to use Max MSP, but soon realized it would be an incredibly difficult project to setup, considering all the various rehearsal spaces we would use, as well as the acoustics in the concert studio. Nonetheless, with a good fixed audio recording, careful orchestration in the piano, and practicing balance with the recording, I was able to accomplish a sound reminiscent of live manipulation in this work.
Keywords: Performance; paper; composition